CAPITALIZING ON THE BOYCOTT WAVE: STRATEGIES FOR MUSLIM ENTREPRENEURS TO SEIZE MARKET OPPORTUNITIES FROM THE BOYCOTT OF PRO-ISRAEL PRODUCTS - John Christianto Simon; Abdul Rokhim; Mahben Jalil; Irwandi Irwandi; Abdullah Rasjid (Branding: Jurnal Manajemen dan Bisnis, 2023)
In an era marked by increasing geopolitical tensions and consumer activism, the boycott of products associated with certain political stances, such as those supporting Israel, has created unique market voids and opportunities. This paper explores strategic avenues for Muslim entrepreneurs to capitalize on these emerging market gaps. Utilizing a mixed-method approach, combining qualitative insights from expert interviews and quantitative market analysis, this study identifies key areas where Muslim entrepreneurs can effectively intervene and thrive. The findings reveal that the boycott movement has led to a demand shift in various sectors, including food, technology, and apparel, presenting ripe opportunities for alternative products and services. This paper proposes a framework for Muslim entrepreneurs to identify these opportunities, develop culturally and ethically aligned products, and employ targeted marketing strategies to capture and expand their market presence. The study not only contributes to the existing literature on market strategies in politically charged environments but also provides practical guidelines for entrepreneurs seeking to navigate and leverage these complex market dynamics. The implications of this research extend beyond immediate market opportunities, suggesting a broader role for entrepreneurial ventures in shaping economic landscapes amidst political and social upheavals.